A Review of Biosensors for Non-Invasive Diabetes Monitoring and Screening in Human Exhaled Breath - Usman, F. (2019)
Exhaled breath acetone has been identified as a diabetes biomarker for non-invasive diagnosis. Its detection using biosensors features has many advantages over the conventional means. This paper reviews the recent literature on the detection of exhaled breath acetone and acetone vapor of diabetic interest. The biosensors have been classified based on their transduction methods. The performance characteristics of the biosensors have been explored for comparison. The future trends are also highlighted. Â© 2013 IEEE.